Pola Komunikasi Guru dan Orangtua dalam Pembentukan Karakter Religius pada Siswa Generasi Z - Al Qodri, Ahmad Miftahudin; Faisal, Ki Agus Muhammad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to find out the communication patterns of teachers and parents at SMAN 1 Depok City, to find out the model for the formation of religious character, to find out the Communication Patterns of teachers and parents in the formation of religious character in generation Z at SMAN 1 Depok City. This study uses a qualitative approach with in-depth interviews and observation methods and uses an interpretive communication paradigm with the socio-psychological communication tradition. The teacher sample taken in forming character is the school principal, vice principal for student affairs, counseling teachers, Islamic Religious Education (PAI) teachers, PPKN teachers, and homeroom teachers. The sample of students was taken from class X and XI, respectively, class 2 students. Meanwhile, the sample of parents was taken from the parents of Class X and XI students from each class. The results of this study are that interpersonal communication has a relationship with the psychology of behaviorism communication in forming religious character, namely through the provision of good attitudes (stimulus), repetition, habituation, and counseling. Communication Patterns of Teachers and Parents at SMAN 1 Depok City through many directions, with teacher or school committee meetings with parents, WhatsApp Groups between teachers (homeroom teachers) and parents and the existence of a new application or media called the Learning Management System (Learning Management System). LMS) where the application can connect teachers, parents and students. The model for forming religious character in generation Z at SMAN 1 Depok City is carried out through giving good attitudes, habituation (sunah dhuha prayers, reading prayers, tadarus before starting learning, midday and afternoon prayers in congregation at the school mosque), training, counseling, and the mandate of the principal or teacher during the Monday ceremony. The conclusion in this study is the pattern of communication between teachers and parents in the formation of religious character at SMAN 1 Depok City, namely by having good interpersonal communication skills between teachers and parents and understanding the psychology of communication so that they can get to know children more closely, so that it becomes a habit or good habit that is formed. both at home and at school. Keyword: Communication Pattern, Teacher Communication, Parent Communication, Religious Character, Generation Z